The impact of carbon disclosure mandates on emissions and financial operating performance - Benedict Downar; Jürgen Ernstberger; Stefan Reichelstein; Sebastian Schwenen; Aleksandar Zaklan (Review of Accounting Studies, 2021)
We examine the impact of a disclosure mandate for greenhouse gas emissions on firms' subsequent emission levels and financial operating performance. For UK-incorporated listed firms a carbon disclosure mandate was adopted in 2013. Our difference-in-differences design shows that firms affected by the mandate reduced their emissions by about 8% relative to a control group of European firms. At the same time, our tests indicate that the treated firms experienced no significant changes in their gross margins. Taken together, our findings indicate that the reporting mandate had a real effect on the variable to be disclosed without adversely affecting the financial operating performance of the treated firms.
Keywords: Q28; Q40; M41; M48; 330; Disclosure of nonfinancial information; Mandatory disclosure; Greenhouse gas emissions; Real effects